Study of Waste Lubricant Hydrocracking into Fuel Fraction over The Combination of Y-Zeolite and ZnO Catalyst - , Fathonatu Anisa Khowatimy ([Yogyakarta] : Elsevier, 2014)
The study of waste lubricant hydrocracking into gasoline and diesel fraction using the combination of Y-Zeolite and ZnO (Y-Zeolite/ZnO) catalyst has been conducted. The hydrocracking of waste lubricant was carried out in a semi-flow stainless steel reactor system (i.d = 3.78 cm